KAWIN TANGKAP DALAM PERSPEKTIF MAQASHID AL-SYARI'AH DAN HUKUM DI INDONESIA: - Habibi Al Amin; Muhdi Muhdi (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2021)
This article is the result of a qualitative field research with a legal sociology approach. This article discusses the tradition of intermarrying with the eyes of Islamic law and positive law. The researcher uses the maqasid shariah theory in explaining the legal position of capture marriage. The maqasid shariah theory has a flexible and adaptive character in determining the legal status of localistic matters. The location of this research is in Pekalongan village, Sampang district, Madura. This study concludes that marriage arrests in the village of Pekalongan are legal, even obligatory, seeing that the implementation of the marriage arrest law cannot be separated from the main purpose of implementing Islamic laws. Capture marriage fulfills the maqashid al-sharī'ah element. Capture marriages function as hifd al din, namely tradition as religious social control, as a social protection system that fulfills the elements of hifdh an-nafs (avoiding cases of violence and vigilantism), hifdh an-nasl (avoiding offspring from illicit relationships), hifdh al-mal (avoiding the use of money in vain), hifdh al-aql (maintaining a healthy mindset and avoiding depression). Capture marriages are marriages that have no legal force because they are not registered.. Keywords: kawin tangkap tradition, maqasid shariah, law DAFTAR PUSTAKA Abu Ishaq al-Syatibi, Al-Muwafaqat fi Ushul al-Ahkam, Juz ke 2, Kairo: Dar al-Fikr, tt. Abu Ishaq al-Syatibi, al-Muwafaqat fi ushul al-Syari’ah, ( Darul Ma’rifah, Beirut, 1997) Ali Qaim, Pernikahan Masalah Dan solusinya, Cet I, Jakarta: Cahya, 2009. Amir Syarifuddin, Ushul Fiqih, Cet 7, Jakarta: Kencana, 2014. Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 Dewi Wulansari, Hukum Adat Indonesia (suatu Pengantar), PT. Refika Aditama, Bandung, 2010. Ibnu Rusyd, Bidayatul Mujtahid Analisa Fiqih para Mujtahid, alih bahasa oleh: Imam Ghazali Said, Ahmad Zaidun, (Jakarta: Pustaka Amani, 2007), Jilid 2. Kajian Ilmiah FKI Ahla, Shuffah, Kamus Fiqih, Kediri: Lirboyo Press, 2016 Lihasanah, Ahsan. 2008. Fiqh al-Maqashid ‘inda al-Syathibi. Mesir: Dar al-Salam. Thahir Maloko. Dinamika Hukum Dalam Perkawinan, Cet. I; Makassar Alauddin University Press, 2012. Syaikh al-‘Allamah Muhammad bin ‘Abdurrahman ad-Dimasyqi, Fiqih Empat Mazhab, Cet II, Bandung: Hasyimi Press, 2004. Syatibi, Abu Ishaq. Al-Muwafaqat fi Ushul al-Syari’ah. Damsyiq: Dar al-Fikr. Thalib, Sayuti. 1974. Hukum Keluarga Indonesia. Jakarta: UU Press. Umar, Hasbi. 2007. Nalar Fiqih Kontemporer. Jakarta: Rineka Cipta. Undang-Undang Perkawinan Indonesia, Kompilasi Hukum Islam tentang Perkawinan. 2007. Penerbit Wippres. Welstead, Mary. 2006. Family Law. New York: Oxford University Press. Zahrah, Abu. 1957. Al-Ahwal al-Syakhshiyyah. Kairo: Dar al Fikr al-Arabi. Zuhaily, Wahbah. 1989. Al-Fiqh al-Islami wa Adillatuhu Juz II. Damsyiq: Dar al-Fikr.